2011
DOI: 10.1007/s00502-011-0812-z
|View full text |Cite
|
Sign up to set email alerts
|

Finite element analysis of permanent magnet synchronous machines with fractional slot tooth coil windings

Abstract: The permanent magnet synchronous machine with an external rotor is the most important device for high performance electrical drive systems in particular for hybrid electric vehicles. The paper discusses finite element analyses of such a machine with concentrated tooth coils in terms of a comparison of both Y-and D-connected stator windings. As the evolved electromagnetic torque is one of the most important design parameter, various ratios of tooth width and slot pitch are analyzed with the two connections of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2012
2012
2017
2017

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 10 publications
1
2
0
Order By: Relevance
“…This variation needs to be considered in drive control schemes, especially in sensorless control schemes, requiring multidimensional lookup tables stored. These findings are similar to those previously reported where the influence of sub-harmonics in certain machine geometries was observed to cause temporal and spacial variation of the d-q-axis inductances in an IPM (interior permanent magnet) motor [23], where it has also been noted the inadequacy of d-q theory [24]. In the case of the synchronous reluctance motor, as the airgap length is small due to its inverse relation with the machine magnetizing inductance, power factor and torque capability, the localized effects caused by the higher order harmonics are increasingly pronounced on the d-q axis inductances…”
Section: 6t 14tsupporting
confidence: 81%
“…This variation needs to be considered in drive control schemes, especially in sensorless control schemes, requiring multidimensional lookup tables stored. These findings are similar to those previously reported where the influence of sub-harmonics in certain machine geometries was observed to cause temporal and spacial variation of the d-q-axis inductances in an IPM (interior permanent magnet) motor [23], where it has also been noted the inadequacy of d-q theory [24]. In the case of the synchronous reluctance motor, as the airgap length is small due to its inverse relation with the machine magnetizing inductance, power factor and torque capability, the localized effects caused by the higher order harmonics are increasingly pronounced on the d-q axis inductances…”
Section: 6t 14tsupporting
confidence: 81%
“…It is observed that, because of the TC-windings, the saturation of TC-PMSMs is position-and time-dependent under the influence of current linkage sub-harmonics. In [17] it is reported that inductances of TC-PMSMs vary with the rotor position. This inductance variation is caused mainly by local saturation effects due to the asynchronous harmonic magnetic fluxes.…”
Section: Local Saturationmentioning
confidence: 99%
“…The paper also analyzes the way the modified 2-segmented halfback array develops its performance in comparison with the classic 2-segmented halfback array model for the outer rotor PMSM with a double-layer and 2nd-grade fractional slot winding [10,11]. All the significant EM perspectives are performed with the gap consideration among the FE models using a design function with a number of constraints.…”
Section: Introductionmentioning
confidence: 99%